Taalmonument – implant języka - Wawrzyniak, Sandra (Człowiek i Społeczeństwo, 2017)
Can a language be successfully implanted from one continent to another? History has recorded similar cases more than once, but only once this operation was commemorated by a monument – a testimony to the presence of the only one “indigenous” Indo-European language on the African continent. The first part of the article will outline the history of the presence of Europeans in South Africa and the key moments affecting its current socio-linguistic situation. The history and development of the Afrikaans language will be described, with particular emphasis on its role in building White South Africa and the Apartheid system. The next part will present the idea and circumstances of the creation of the Taalmonument – a monument dedicated to the Afrikaans language. It will discuss its individual elements and their characteristics from the viewpoint of the Apartheid ideology. In the next part, the author will present the reaction of the black population of South Africa to the creation of the monument, and the controversy surrounding this building after the overthrow of the system, on the basis of a strongly existing revisionist discourse. In conclusion, the author will present possible new readings of old content and ideas related to the development and maintenance of Taalmonument.